Extrapolation of scattering data to the negative-energy region. III. Application to the p-16O system - Blokhintsev, L.; Kadyrov, Alisher; Mukhamedzhanov, A.; Savin, D. (The American Physical Society, 2018)
The problem of analytic continuation of the scattering data to the negative-energy region to obtain information on asymptotic normalization coefficients (ANCs) of bound states is discussed. It is shown that a recently suggested method [O. L. Ramírez Suárez and J.-M. Sparenberg, Phys. Rev. C 96, 034601 (2017)] is not strictly correct in the mathematical sense since it is not an analytic continuation of a partial-wave scattering amplitude to the region of negative energies. However, it can be used for practical purposes for sufficiently large charges and masses of colliding particles. Both the method and the standard method of continuing of the The problem of analytic continuation of the scattering data to the negative-energy region to obtain information on asymptotic normalization coefficients (ANCs) of bound states is discussed. It is shown that a recently suggested Δ method [O. L. Ramírez Suárez and J.-M. Sparenberg, Phys. Rev. C 96, 034601 (2017)] is not strictly correct in the mathematical sense since it is not an analytic continuation of a partial-wave scattering amplitude to the region of negative energies. However, it can be used for practical purposes for sufficiently large charges and masses of colliding particles. Both the Δ method and the standard method of continuing of the effective range function are applied to the p16O system, which is of interest for nuclear astrophysics. The ANCs for the ground 5/2+ and excited 1/2+ states of 17F are determined.